Recent Advances in the Use of Focused Ultrasound for Magnetic Resonance Image-Guided Therapeutic Nanoparticle Delivery to the Central Nervous System - Fisher, Delaney G.; Price, Richard J. (Frontiers in Pharmacology, 2019)
Targeting systemically-administered drugs and genes to specific regions of the central nervous system (CNS) remains a challenge. With applications extending into numerous disorders and cancers, there is an obvious need for approaches that facilitate the delivery of therapeutics across the impervious blood-brain barrier (BBB). Focused ultrasound (FUS) is an emerging treatment method that leverages acoustic energy to oscillate simultaneously administered contrast agent microbubbles. This FUS-mediated technique temporarily disrupts the BBB, allowing ordinarily impenetrable agents to diffuse and/or convect into the CNS. Under magnetic resonance image guidance, FUS and microbubbles enable regional targeting—limiting the large, and potentially toxic, dosage that is often characteristic of systemically-administered therapies. Subsequent to delivery across the BBB, therapeutics face yet another challenge: penetrating the electrostatically-charged, mesh-like brain parenchyma. Non-bioadhesive encapsulated nanoparticles can help overcome this additional barrier to promote widespread treatment in selected target areas. Furthermore, nanoparticles offer significant advantages over conventional systemically-administered therapeutics. Surface modifications of nanoparticles can be engineered to enhance targeted cellular uptake, and nanoparticle formulations can be tailored to control many pharmacokinetic properties such as rate of drug liberation, distribution, and excretion. For instance, nanoparticles loaded with gene plasmids foster relatively stable transfection, thus obviating the need for multiple, successive treatments. As the composition, size, and safety of these nanoparticles can vary greatly, this review article provides an overview of FUS coupled with non-viral nanoparticles currently utilized for drug delivery to the brain.